(untitled) (Dhaka University Journal of Biological Sciences, 2012)
Surface-water gley soils comprise extensive area on the seasonally wet landscape of Meghna floodplain in Bangladesh. Three typical surface-water gley soils from the above floodplain were studied in the field and laboratory for their pedogenesis. Morphological properties indicate that there is formation of gleyed/ pseudogleyed horizons in the soil profiles. Extensive development of mottles, ploughpans and flood coatings or gleyans is the most notable morphogenetic features in these soils. Physically, these soils are medium to fine textured where textural class ranged between silt loam and silty clay. Chemically, the soils are moderately acidic to neutral in reaction with seasonally fluctuating pH in the surface horizon. The ΔpH values are all negative and range from – 0.90 to – 2.01. The organic matter content in the surface soil is relatively low that decreases steadily with depth. The cation exchange capacity (CEC) of the soils ranged from 3.53 to 14.08 cmol p+/kg with an average of 10.10 cmol p+/kg and base saturation per cent (BSP) varied from 59 to 86. The Ca++/Mg++ ratio is less than unity indicating loss of Ca++ due to gleization in these soils.